Costs Related to Frontotemporal Dementia in Latin America: A Scoping Review of Economic Health Studies - Alva-Dìaz, Carlos; Malaga, Marco; Rodriguez-Calienes, Aaron; Morán-Mariños, Cristian; Velásquez-Rimachi, Victor; Custodio, Nilton (Frontiers in Neurology, 2021)
Introduction: Frontotemporal dementia (FTD) is a complex syndrome characterized by changes in behavior, language, executive control, and motor symptoms. Its annual economic burden per patient in developed countries has been classified as considerable, amounting to US$119,654 per patient, almost double the patient costs reported for Alzheimer's disease. However, there is little information regarding cost-of-illness (COI) for FTD in Latin-America (LA). Aim: To describe the costs related to FTD in LA. Methods: We included COI studies on FTD conducted in LA published in English, Spanish, or Portuguese from inception to September 2020. We carried out a systematic search in Pubmed / Medline, Scopus, Web of Science, Scielo, Cochrane, and gray literature. For quality assessment, we used a COI assessment tool available in the literature. All costs were reported in USD for one year and adjusted for inflation. Results: We included three studies from Argentina, Brazil, and Peru. Direct costs (DCs) included medication (from US$959.20 to US$ 4,279.20), health care costs (from US$ 2,275.80 to US$7,856.16), and caregiver costs (from US$9,634.00 to US$28,730.28). Indirect costs (ICs) amounted to US$43,076.88. Conclusions: In LA countries, the reporting of costs related to FTD continues to be oriented towards DCs. They remain lower than in developed countries, possibly due to the limited health budget allocated. Only one Brazilian report analyzed ICs, representing the highest percentage of the total costs. Therefore, studies on the COI of this disease in LA are essential, focusing on both out-of-pocket spending and the potential economic loss to patients' homes and families.